Microwave-assisted catalyzed glycerol etherification into polyglycerol in the presence of alkaline modified aluminum pillared clay - SAJID, MUHAMMAD (2019)
The potential of glycerol conversion into a valuable product such as polyglycerol was examined through the microwave assisted catalytic etherification process. This study revealed the achievement of a nonconventional heating method for glycerol etherification via modified aluminum pillared clay (AlPC).